Complex-Valued Least Mean Kurtosis Adaptive Filter Algorithm - Menguc, Engin Cemal; Acır, Nurettin (Ieee, 2016)
In this study, a complex-valued least mean Kurtosis (CLMK) adaptive filter algorithm is designed for processing complex-valued signals. The performance of the designed algorithm is tested on a complex-valued system identification and compared the complex-valued least mean square (CLMS) and complex-valued normalized least mean square (CNLMS) algorithms. As a result, the CLMK algorithm shows a higher performance than the other algorithms in terms of the convergence rate, mean square error (MSE) and mean square deviation (MSD).
24th Signal Processing and Communication Application Conference (SIU) -- MAY 16-19, 2016 -- Zonguldak, TURKEY
Menguc, Engin Cemal/0000-0002-0619-549X
Keywords: complex-valued adaptive filter; complex-valued system identification; complex-valued least mean Kurtosis algorithm